Crystalloid Pre-Load or Co-Load In Prevention of Spinal Anaesthesia Induced Hypotension In Caesarean Section-A Comparative Study - Mohammad, Taneem; Alam, Md Tanveer; Bajracharya, Gaurav Ratna; Hossain, Md Mozaffer; Rahman, Md Abdur (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Abstract not available JBSA 2016; 29(2):45-53